A Preliminary, Multicenter, Prospective and Real World Study on the Hemostasis, Coagulation, and Safety of Hemocoagulase Bothrops Atrox in Patients Undergoing Transurethral Bipolar Plasmakinetic Prostatectomy - Li, Bing-Hui; Yu, Zhao-Jun; Wang, Chao-Yang; Zi, Hao; Li, Xiao-Dong; Wang, Xing-Huan; Ren, Xuan-Yi; Liu, Tong-Zu; Zheng, Hang (Frontiers in Pharmacology, 2019)
Objective: To evaluate the hemostasis and coagulation effect of Hemocoagulase Atrox in benign prostatic hyperplasia (BPH) patients undergoing transurethral bipolar plasmakinetic prostatectomy (TUPKP). Methods: This study adopted a multicenter, prospective, and real world design. BPH patients undergoing TUPKP were divided into two groups according to whether they adopted Hemocoagulase Atrox (group B) or not (group A) during perioperative period. The electronic clinical data on every included subject, including the international prostate symptom score (IPSS) and the quality of life scale (QoL), maximum urinary flow rate (Qmax), complete blood count, coagulation screening test and adverse events, were measured and compared between the two groups. Results: Finally, 695 patients, 443 in Group A and 252 in group B, were included. Baseline characteristics showed no significant difference between two groups. In group A, compared with baseline, IPSS decreased by 15.66 (95% CI = -16.45 ~ -14.87), QoL decreased by 3.08 (95% CI = -3.30 ~ -2.87), prothrombin time prolonged by 1.02 s (95% CI = 0.56 ~ 1.48), while white blood cells, neutrophils and lymphocytes also significantly changed; white blood cells, neutrophils and platelets increased, while lymphocytes decreased by 0.14×109/L (95% CI = -0.21 ~ -0.08) before discharge. In group B, IPSS decreased by 16.12 (95% CI= -17.02 ~-15.21), QoL decreased by 3.32 (95% CI= -3.56 ~ -3.07), and white blood cells, neutrophils and lymphocytes were also significantly changed, along with white blood cells and lymphocytes that tested before discharge (P< 0.001). After adjustment, transfusion risk was similar in the two groups (OR = 1.582, 95%CI= 0.552 ~ 4.538). Parameters had no substantial difference between the two subgroups whether prostate volume was more than 80 ml or not. Conclusion: Hemocoagulase Atrox is probably safe among BPH patients undergoing TUPKP, exhibiting fine hemostasis and coagulation efficacy, and would not be influenced by prostate volume.